Biodegradable shape memory polymers functionalized with anti-biofouling interpenetrating polymer networks. Issue 32 (27th July 2016) - Dueramae, I.; Nishida, M.; Nakaji-Hirabayashi, T.; Matsumura, K.; Kitano, H.
Abstract : A novel type of shape memory polyurethane (SMPU) with high mechanical properties and biodegradability was constructed using a lactone copolymer (poly(ε-caprolactone- co -γ-butyrolactone), PCLBL), a diol- or triol-based chain extender (1, 5-pentanediol, glycerol and 2-amino-2-hydroxymethyl-1, 3-propanediol) and a diisocyanate cross-linker (1, 6-hexamethylene diisocyanate). Abstract : A novel type of shape memory polyurethane (SMPU) with high mechanical properties and biodegradability was constructed using a lactone copolymer (poly(ε-caprolactone- co -γ-butyrolactone), PCLBL), a diol- or triol-based chain extender (1, 5-pentanediol, glycerol and 2-amino-2-hydroxymethyl-1, 3-propanediol) and a diisocyanate cross-linker (1, 6-hexamethylene diisocyanate). All types of SMPUs possessed high mechanical properties, and the shape recovery test indicated that the SMPU sheets prepared using a triol-chain extender with an amine group recovered completely the original shape at 80 °C. Moreover, the degradation products of the SMPUs were innoxious, which is an important property for use in the biomedical field. Furthermore, the SMPU sheets were interpenetrated with a zwitterionic polymer, poly(carboxymethyl betaine) (PCMB), using the interpenetrating polymer network (IPN) method to additionally introduce an anti-biofouling property. Water contact angle measurements of the surface of PCMB-introduced SMPU sheets showed a drastic reduction from 87° to approximately 30° due to the exposure of the PCMB chains from the SMPU sheets. These SMPU-IPN sheets suppressed significantly both protein adsorption and cell adhesion. Consequently, the PCLBL-PU-based SMPUs interpenetrated with PCMB are promising materials for biomedical devices because of their high mechanical, shape memory, biodegradable, and anti-biofouling properties. These materials are expected to be applied to biomaterials such as embolization materials for aneurysms and a novel type of membrane for postoperative adhesion prevention.